Singlet Orbital Ordering in Bilayer Sr3Cr2 O7 - Jeanneau, Justin (2017)
We perform an extensive study of Sr3Cr2O7, the n=2 member of the Ruddlesden-Popper Srn+1CrnO3n+1 system. An antiferromagnetic ordering is clearly visible in the magnetization and the specific heat, which yields a huge transition entropy, Rln(6). By neutron diffraction as a function of temperature we have determined the antiferromagnetic structure that coincides with the one obtained from density functional theory calculations. It is accompanied by anomalous asymmetric distortions of the CrO6 octahedra. Strong coupling and Lanczos calculations on a derived Kugel-Khomskii Hamiltonian yield a simultaneous orbital and moment ordering. Our results favor an exotic ordered phase of orbital singlets not originated by frustration.